CORRELATION BETWEEN FINANCIAL STRESS AND BURNOUT IN FARMERS: IMPLICATION FOR FOOD INSECURITY, NIGERIA (IJOVTECH, 2026)
The current economic climate has impacted every aspect of people's abilities. Several writers have emphasized the ongoing pattern and prospects of financial stress caused by Nigeria's current economic realities. However, the impact of financial stress on farmers' exhaustion is poorly understood. This study examined farmers in Ebonyi state, Nigeria, to see if financial stress affected their burnout experiences. A total of one hundred and eleven farmers participated in the research. They completed a self-report measure of the Maslach Burnout Inventory (MBI) developed by Maslach et al. (2018) and the Financial Stress Scale (FSS) developed by Northern et al. (2010). Data were analyzed using the statistical package for social sciences SPSS, Version 23. The result of a linear regression indicated that financial stress statistically predicted farmers' burnout F (1,109), 32.31 P< .05, with an R2 of 213. In particular, the result revealed that financial stress accounted for about 21.3% of the variation in farmers' burnout. The finding offers valuable data to psychologists and counselors interested in improving farmers' resilience.